THE INFLUENCE OF STORE ATMOSPHERE, DIGITAL MARKETING, AND BRAND IMAGE ON CONSUMER PURCHASING DECISIONS AT DINO THAI TEA JEPARA - Ayuni, Rissa Qurota; Suharti, Suharti (Economics and Business International Conference Proceeding, 2024)
This research aims to obtain empirical evidence and be able to analyze the influence of store atmosphere, digital marketing, and brand image on consumer purchasing decisions. The population in this research are consumers who visited and purchased Dino Thai Tea Jepara products during October-December 2023. The total sample used in this research was 100 respondents using accidental sampling technique. The data analysis technique used is multiple linear regression. So it can be partially concluded that all independent variables have a positive and significant effect on consumer purchasing decisions. The F value is 41.702 with F table of 2.699 and a significance value of 0.000. A significance value of less than 0.05 indicates that the regression model is significant and can be used to predict the dependent variable. The R Square value obtained is 0.552, which means that 55.2% of the variation in consumer purchasing decisions can be explained by the independent variables store atmosphere, digital marketing and brand image. Meanwhile, the remaining 44.8% is explained by other factors.